2010
DOI: 10.1093/chemse/bjq007
|View full text |Cite
|
Sign up to set email alerts
|

Tmem16b is Specifically Expressed in the Cilia of Olfactory Sensory Neurons

Abstract: Calcium-activated chloride channels (CaCCs) are involved in many physiological processes, including sensory signal transduction, but only little is known to date about their structure and function. We performed a proteome analysis of the olfactory epithelium (OE) membrane proteome and identified so far uncharacterized membrane proteins as candidate channels. One of the most abundant membrane proteins in olfactory sensory neurons (OSNs) was Tmem16b, a member of a recently identified family of CaCCs. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
85
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 22 publications
14
85
0
2
Order By: Relevance
“…Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
Section: Disruption Of Ano2 and Ano2 Expression Patternsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
Section: Disruption Of Ano2 and Ano2 Expression Patternsupporting
confidence: 92%
“…Our N-terminal antibody did not detect a truncated protein in Ano2 -/-tissue, suggesting the occurrence of nonsensemediated mRNA decay, instability of the truncated protein, or both. Ano2 -/-mice were born at Mendelian ratio; they grew, mated, and survived normally and lacked an immediately apparent phenotype.Consistent with previous data [21][22][23] , western blots indicated that Ano2 is most highly expressed in olfactory epithelium (MOE and VNO) and eye tissue (Fig. 1a,b).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…A molecular understanding of the dual regulation of CaCCs by voltage and Ca 2+ has recently become possible with the discovery that Ano1 (TMEM16a) is an essential subunit of CaCCs. Ano1 can be gated by Ca 2+ (1,2), including epithelial secretion (3,4), sensory transduction and adaptation (5)(6)(7)(8), regulation of smooth muscle contraction (9), control of neuronal and cardiac excitability (10), and nociception (11). This myriad of functions has attracted attention for more than 25 years (12,13), but a lack of consensus regarding their molecular composition has stymied a mechanistic understanding of their gating.…”
Section: +mentioning
confidence: 99%
“…Its molecular correlate has recently been identified as TMEM16A/anoctamin1 (Amjad et al 2015), the founding member of the anoctamin family of Ca 2+ -activated Cl − channels (Caputo et al 2008;Schroeder et al 2008;Yang et al 2008). While different groups have demonstrated expression of both anoctamin1 and anoctamin2 in VSNs (Rasche et al 2010;Billig et al 2011;Dauner et al 2012;Dibattista et al 2012), vomeronasal Ca 2+ -activated Cl − currents were abolished in conditional anoctamin1 null mice (Amjad et al 2015). For interpretation of these results, however, it is essential to determine whether vomeronasal Cl − channels contribute a strongly depolarizing current or, by contrast, if anoctamin1 activation mediates membrane hyperpolarization or shunting inhibition.…”
Section: +mentioning
confidence: 99%